Agenda de políticas públicas nos governos Dilma e Temer: suas características e a relação com o plano de governo - Andrade, João Vitor dos Santos (2021)
This research is part of the field of study of public policies, more precisely the stage of setting priorities and forming the government agenda (policy agenda-setting). From the theoretical and methodological framework developed and improved over the last decades by researchers in the field, with emphasis on the theory of Punctuated Equilibrium by Baumgartner and Jones (1993) and the Multiple Streams model by Kingdon (2014), we studied the variation on the governmental agenda of the presidency of the Republic under the governments of Dilma Rousseff and Michel Temer (2015-2018). The period that encompasses the research was marked by an impeachment that changed the composition of the government, changing both the actors present in this sphere of decision (turnover) as well as the agenda of priorities in public policies. The objective of the study was to highlight points of proximity and distance between the attention given to public problems at both times and to compare them with the Government Plan, a document that contains the agenda released to voters during the electoral campaign, pointing out what has changed and what causes of change. Thus, we analyzed the variation in attention over time based on the data obtained through the content analysis of normative and non-normative documents related to the government and the candidacy of the elected slate. From the results, we can see that in the agenda presented during the election there was a high attention to issues related to macroeconomics, a characteristic that remained on the agenda of both governments with a continuous increase year after year, albeit with a change in specificities. Issues related to social policies and civil rights, on the other hand, have seen a reduction in attention. The effects of the economic and political crises had an impact on the agenda, leaving economic and administrative issues in evidence and taking away the centrality of the others, in addition to reducing the diversity of the agenda that started to focus on a reduced number of issues.